PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR IPA SISWA KELAS V SDN 143 PALEMBANG - Naia Nur Anjani; Ilham Arvan Junaidi; Ana Theriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low motivation of students to learn which is seen from the lack of enthusiasm in participating in learning, low student participation during the learning process, and lack of enthusiasm in completing the tasks given by the teacher so that learning has not run optimally. This study aims to determine whether there is an influence of the problem based learning model on the motivation to learn science in grade V students of SD Negeri 143 Palembang. The population in this study were grade V students of SD Negeri 143 Palembang. The sample in this study were students of class VA as the control class and class VC as the experimental class with a total of 30 students in each class. The type of research used is experimental research with a quasi-experimental research method (quasi-experimental) with a Non-Randomized Pretest-Posttest Control Group Design. The data collection technique in this study used questionnaires and documentation. The instrument used in the student learning motivation test was a questionnaire. The data analysis technique in this study used the t-test (independent sample t-test) assisted by SPSS 22. The results of this study indicate that there is student learning motivation in learning science in grade V SD Negeri 143 Palembang. Judging from the t-test data analysis calculations, the sig (2-tailed) value obtained was 0.000 < 0.05, so Ha is accepted